Intraoperative Neuromonitoring in Predicting Neurological Deficits in Patients with Intramedullary Lesions in a Tertiary Care Center in Nepal - Rajbhandari, Binod; Kafle, Prakash; Pradhanang, Amit B; Sedain, Gopal; Shilpakar, Sushil K; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2022)
Introduction Intramedullary spinal cord lesions (IMSCL) constitute 20%–30% of all spinal cord lesions. There is still uncertainty regarding the usefulness of intraoperative neuromonitoring (IONM) during spinal surgery. The purpose of this study is to determine the effectiveness of IONM in patients undergoing intramedullary spinal surgery. Methods Twenty-three patients who underwent surgery at the Department of Neurosurgery, Tribhuvan University Teaching Hospital from January 2017 to December 2020 were included. Somatosensory evoked potential, transcranial motor evoked potentials and electromyography were recorded. Patients were divided into three groups based on IONM parameters: 1. one with no drop 2. one with a decrease and a recovery during surgery, and 3. one with a decrease but no recovery. The duration of follow-up was six months. Results Neurological improvement was noted in 14 patients, stable in 4, and worse in 5. Out of 14 patients with clinical improvement, 9 had no decrease in IONM, while 5 had a temporary decrease. Among 4 patients whose postoperative status remained unchanged, 2 had no decrease in IONM, while one had a temporary decrease and one has a sustained decrease. Among 5 patients who deteriorated postoperatively, 1 had no decrease in IONM, and 4 had a decrease without recovery. During surgery, patients who demonstrated monitoring alterations but reverted to baseline had better neurological outcomes than those who did not (p=0.045). Conclusion Our findings support that IONM is an effective tool for the safe resection of IMSCL. Further multi-centric larger studies are recommended to gain more insight into IONM.